2012
DOI: 10.1051/0004-6361/201219107
|View full text |Cite
|
Sign up to set email alerts
|

Photometric reverberation mapping of 3C 120

Abstract: We present the results of a five month monitoring campaign of the local active galactic nuclei (AGN) 3C 120. Observations with a median sampling of two days were conducted with the robotic 15 cm telescope VYSOS-6 located near Cerro Armazones in Chile. Broad band (B, V) and narrow band (NB) filters were used in order to measure fluxes of the AGN and the Hβ broad line region (BLR) emission line. The NB flux is constituted by about 50% continuum and 50% Hβ emission line. To disentangle line and continuum flux, a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 37 publications
3
63
0
Order By: Relevance
“…The proposed technique of microlensing-aided reverberation mapping aims at taking advantage of this effect to measure the time lag between the continuum and broad line variations. Our method is not conceptually very different from photometric reverberation mapping (Haas et al 2011;Chelouche & Daniel 2012;Chelouche & Zucker 2013;Pozo Nuñez et al 2012;Edri et al 2012;Zu et al 2014;Bachev et al 2014). In that case, multi-band photometry is used to disentangle the flux of the continuum and of the BLR, while our technique can already be applied to singleband data.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed technique of microlensing-aided reverberation mapping aims at taking advantage of this effect to measure the time lag between the continuum and broad line variations. Our method is not conceptually very different from photometric reverberation mapping (Haas et al 2011;Chelouche & Daniel 2012;Chelouche & Zucker 2013;Pozo Nuñez et al 2012;Edri et al 2012;Zu et al 2014;Bachev et al 2014). In that case, multi-band photometry is used to disentangle the flux of the continuum and of the BLR, while our technique can already be applied to singleband data.…”
Section: Introductionmentioning
confidence: 99%
“…We combined the RoBoTT telescope data (Pozo Nuñez et al 2012) with new data from the BEST II (Kabath et al 2009). …”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Because the narrow-band collects both the emission line flux and the underlying continuum, the challenge is to extract the pure emission line light curve. In the dedicated case study of 3C 120, Pozo Nuñez et al (2012) demonstrated that PRM reaches an accuracy similar to spectroscopic RM (Grier et al 2012).…”
Section: Introductionmentioning
confidence: 95%
“…An advantage is that it does not require high spatial resolution imaging and can be applied directly to the monitoring data. Recently, FVG has been tested on PRM data (Haas et al 2011;Pozo Nuñez et al 2012). These tests show that by using a well defined range for the host galaxy slope (Sakata et al 2010) it is possible to separate the AGN contribution at the time of the monitoring campaigns.…”
Section: Introductionmentioning
confidence: 99%